2010
DOI: 10.1021/jf903787s
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of the Neonicotinoid Insecticides Acetamiprid and Thiacloprid by the Yeast Rhodotorula mucilaginosa Strain IM-2

Abstract: A yeast identified as Rhodotorula mucilaginosa strain IM-2 was able to degrade acetamiprid (AAP) and thiacloprid (THI) in sucrose mineral salt medium with half-lives of 3.7 and 14.8 days, respectively, while it did not degrade imidacloprid and imidaclothiz. Identification of metabolites indicated that R. mucilaginosa IM-2 selectively converted AAP and THI by hydrolysis of AAP to form an intermediate metabolite IM 1-3 and hydrolysis of THI to form an amide derivative, respectively. Metabolite IM 1-3 had no inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 36 publications
4
47
2
Order By: Relevance
“…44 Rhodotorula mucilaginosa strain IM-2 converts ACE to the N-acetyl derivative of 6-chloropyridinyl-3-methylamine and hydrolyzes THI to the corresponding Journal of Agricultural and Food Chemistry ARTICLE N-carbamoylimine. 45 The toxicology of the metabolites is an important factor in the effectiveness of detoxification.…”
Section: ' Compounds and Substituentsmentioning
confidence: 99%
“…44 Rhodotorula mucilaginosa strain IM-2 converts ACE to the N-acetyl derivative of 6-chloropyridinyl-3-methylamine and hydrolyzes THI to the corresponding Journal of Agricultural and Food Chemistry ARTICLE N-carbamoylimine. 45 The toxicology of the metabolites is an important factor in the effectiveness of detoxification.…”
Section: ' Compounds and Substituentsmentioning
confidence: 99%
“…The above results indicated that the significant, different aspect of neonicotinoid insecticides for soil use was related to their special building block, which was transformed by soil microbes into different insecticidal metabolites. Further bioremediation in situ indicated that the inoculated yeast R. mucilaginosa strain IM‐2 showed low biodegradation of AAP and THI in soil,16 and even inoculated S. maltophilia CGMCC 1.1788 in soil did not show any capacity for biodegradation of IMI, IMT, AAP and THI (unpublished data). It seems that soil microbes are diverse, complex, intact and cooperative, and the bioefficacy of the metabolites should consist of long‐lasting insecticidal activity against horsebean aphid, in concert with the remaining parent residual activity.…”
Section: Introductionmentioning
confidence: 98%
“…Most of these metabolites showed insecticidal activity at the ppm level, but a lower activity than the parent compounds against horsebean aphid, except for the olefin IMI, formed by eliminating water from 5‐hydroxy IMI, which showed 19 times higher bioefficacy than IMI 12–15. The yeast Rhodotorula mucilaginosa strain IM‐2 particularly degraded AAP and THI in the position of the cyanoguanidine pharmacophore to form metabolites IM‐1‐3 and THI amide respectively, while it did not degrade IMI and IMT in the position of the nitroguanidine pharmacophore 16. The AAP metabolite IM‐1‐3 had no insecticidal activity, and the THI amide showed more than 10 times lower activity against A. craccivora than the parent compound THI.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the yeast Rhodotorula mucilaginosa IM-2 transformed AAP to IM-1-3. 15 The bacterium Ensifer meliloti CGMCC 7333 degraded AAP to IM-1-2.…”
Section: Introductionmentioning
confidence: 99%